GENERATION Z CONSUMERS’ MOTIVES AND BARRIERS TO PURCHASING ORGANIC FOOD PRODUCTS IN SERBIA - Vehapi, Semir; Mitic, Sanja (Economics of Agriculture, 2021)
The aim of this study is to identify and analyze the main motives and barriers for purchasing organic food in the Generation Z market segment in Serbia. A quantitative study was conducted through a survey questionnaire filled out by 213 students from three universities. The results are based on descriptive statistics, the independent samples t-test and the analysis of variance. Quality and health protection and improvement are identified as the primary motives for purchasing organic food, proving that egoistic motives prevail over altruistic ones. The most important barriers hindering organic food consumption are high price, lack of information, and limited availability. The willingness of Generation Z members to accept high market prices for organic food depends on their monthly household income. These findings could be used by organic food producers and retailers to predict buying behavior and adapt their promotional activities on the Serbian market.